COVID-19 vaccination acceptability in the UK at the start of the vaccination programme: a nationally representative cross-sectional survey (CoVAccS – wave 2). (January 2022) - Sherman, S.M.; Sim, J.; Cutts, M.; Dasch, H.; Amlôt, R.; Rubin, G.J.; Sevdalis, N.; Smith, L.E.
Abstract: Objectives: Investigate factors associated with the intention to have the COVID-19 vaccination following initiation of the UK national vaccination programme. Study design: An online cross-sectional survey completed by 1500 adults (13th–15th January 2021). Methods: Linear regression analyses were used to investigate associations between intention to be vaccinated for COVID-19 and sociodemographic factors, previous influenza vaccination, attitudes and beliefs about COVID-19 and COVID-19 vaccination and vaccination in general. Participants' main reasons for likely vaccination (non-)uptake were also solicited. Results: 73.5% of participants (95% CI 71.2%, 75.7%) reported being likely to be vaccinated against COVID-19, 17.3% (95% CI 15.4%, 19.3%) were unsure, and 9.3% (95% CI 7.9%, 10.8%) reported being unlikely to be vaccinated. The full regression model explained 69.8% of the variance in intention. Intention was associated with: having been/intending to be vaccinated for influenza last winter/this winter; stronger beliefs about social acceptability of a COVID-19 vaccine; the perceived need for vaccination; adequacy of information about the vaccine; and weaker beliefs that the vaccine is unsafe. Beliefs that only those at serious risk of illness should be vaccinated and that the vaccines are just a means for manufacturers to make money were negatively associated with vaccination intention. Conclusions: Most participants reported being likely to get the COVID-19 vaccination. COVID-19 vaccination attitudes and beliefs are a crucial factor underpinning vaccine intention. Continued engagement with the public with a focus on the importance and safety of vaccination is recommended.